Urdimbres, redes y tejidos. Espacio Territorial de Capacitación y Reincorporación (ETCR) de Icononzo, Tolima (Colombia). - JARAMILLO HINCAPIÉ, Jorge Iván (Chasqui (13901079))
In this article we address some findings and the research methodology in a Space for Training and Reincorporation, a territorial figure product of the Peace Agreement in Colombia. All within the framework of the research "Subjectivities and community economies, a dialogue of experiences in the Territorial Space of Training and Reincorporation of Icononzo, Tolima". Throughout the country, these spaces have become production plants, experimental laboratories for new ways of living and inhabiting the world, a whole framework that allows us to recognize the reinsertion process of hundreds of men and women who reverse their own history.